Development of an information literate school community: Perceived roles and practices of teacher librarians - Aisah, M.A.; Abrizah, Abdullah; Yanti Idaya Aspura, M.K.; Wan Dollah, Wan Abd Kadir (Faculty of Computer Science and Information Technology, University of Malaya, 2018)
The research investigates the perceived roles and practices of teacher librarians in developing an Information Literate School Community (ILSC). The study employs a survey method, which was based on a set of an ILSC benchmarks developed by Henri (1995). A web-based questionnaire was e-mailed to 148 teacher librarians from Malaysian secondary schools in which their School Resource Centers (SRCs) received 4 and 5 stars rating for the year 2015 SRCs evaluation. The result showed that the teacher librarians rated 11 roles as being important, however they acknowledged that they have successful (very much) in executing only one task in their practice that is they "ensure that teachers are efficient library users". Teacher librarians evaluated the information services as very important and at the same time, they thoroughly practiced their roles as the stakeholder in terms of delivering and providing information services to the school community. The finding also revealed that the integration of ICT was recorded as having the highest mean gap between perceived roles and practices. This indicated that although teacher librarians had placed integrating ICT as an important role, there was still a lack of practice. Furthermore, this study has attempted to bridge the apparent divide in the practices of information literacy and the perception of the role in developing an ILSC.